Traditional organizations and economic development : studies of indigenous cooperatives in Liberia - Seibel, Hans Dieter; Massing, Andreas (New York : Praeger Publishers, 1974)
This book is about multitude of indigenous formal and informal organizations all over Africa, often of ancient origin.
Includes bibliographical references: p. 262-263.
oo 25/10/2018
Loans
Keywords: Cooperation